Optimasi Metode Analisis Kadar Surfaktan Anion Menggunakan Methylen Blue Active Subtances dengan Spektrofotometer Ultraviolet Visible - Pratiwi, Endiyana; Prasetya, Agung Tri (Universitas Negeri Semarang, 2020)
The method of analyzing the levels of Linear Alkylbenzene Sulfonate through optimization of various variations including; pH; complex stability time; and the effect of the amount of boric acid interference by using a UV-Vis spectrophotometer with a wavelength of 651 nm. The optimization results show that Linear Alkylbenzene Sulfonate is optimal under conditions of pH 5.98. Linear Alkylbenzene Sulfonate was stable until 60 minutes to minutes without any color concentration and no precipitate appeared, then it did not affect the boric acid interference in the Linear Alkylbenzene Sulfonate of 0.008 mmol. The optimization results will be used to determine the level Linear Alkylbenzene Sulfonate in the application using laundry waste. The application of the results of optimization into laundry waste shows that there are 1.6, 3.08, and 4.18% of Linear Alkylbenzene Sulfonate levels used in laundry services today. These results can be said that the level of Linear Alkylbenzene Sulfonate in this sample of laundry waste has exceeded the standard set by the Government Regulation which is equal to 1.18, 1.23, and 1.10 mg / L.